2019
DOI: 10.1111/1911-3846.12482
|View full text |Cite
|
Sign up to set email alerts
|

The Informativeness of Relative Performance Information and Its Effect on Effort Allocation in a Multitask Environment

Abstract: Prior research documents that providing relative performance information (RPI) motivates employees to increase effort; however, a potential downside of RPI is that it also motivates employees to distort their effort allocations between tasks such that it can be detrimental to overall firm performance. This study investigates via an experiment how the informativeness of RPI affects employees' effort allocations and performance in a multitask environment. We investigate the informativeness of two RPI design choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 61 publications
2
21
0
1
Order By: Relevance
“…One factor of theoretical and practical importance is the task context. Previous feedback research in this area has focused on task complexity (Brown et al 2016;Buchheit et al 2012;Trotman 2005, 2008) and task dimensions (multidimensional vs. one-dimensional tasks) in a single-task environment (Christ et al 2016) or multi-task environments (Hannan et al 2013(Hannan et al , 2019. Overall, these studies confirm the importance of considering the task context when examining feedback effectiveness.…”
Section: Performance Feedback and Goal Settingsupporting
confidence: 52%
See 1 more Smart Citation
“…One factor of theoretical and practical importance is the task context. Previous feedback research in this area has focused on task complexity (Brown et al 2016;Buchheit et al 2012;Trotman 2005, 2008) and task dimensions (multidimensional vs. one-dimensional tasks) in a single-task environment (Christ et al 2016) or multi-task environments (Hannan et al 2013(Hannan et al , 2019. Overall, these studies confirm the importance of considering the task context when examining feedback effectiveness.…”
Section: Performance Feedback and Goal Settingsupporting
confidence: 52%
“…By identifying the state of completion as an important determinant of the effectiveness of feedback, our results contribute to the stream of research that examines the effects of feedback (Buchheit et al 2012;Kluger and DeNisi 1996). Extant management accounting research on feedback and task-characteristics has focused on task complexity (Brown et al 2016;Buchheit et al 2012) or on multi-task environments (Hannan et al 2013(Hannan et al , 2019. In this vein, our findings have practical implications for management accountants who design control systems.…”
Section: Discussionmentioning
confidence: 74%
“…In developing our hypotheses, we also argue that social comparisons increase in the presence of performance category labels and that this increase is even more pronounced when combined labels are used, rather than positive‐only labels. We capture relative performance concerns via three postexperimental questions, as suggested by prior research (Hannan et al 2013, 2019; Tafkov 2013). 23 Table 4, panel A, shows the participants' responses to the respective questions and our aggregated measure Social Comparison Factor (eigenvalue = 1.90; explained variance = 63.4%).…”
Section: Resultsmentioning
confidence: 99%
“…These studies extend the discussion on externally led benchmarking and associated relative performance information (RPI) use within the context of LG. On the other hand, internally generated RPI design and use in relation to personnel controls has been studied in other contexts (Hannan et al , 2013, 2019; Hecht et al , 2019; Mahlendorf et al , 2014). Studies have shown that RPI design choices influence effort distortion (Hannan et al , 2013, 2019) and perceived organisational support (Mahlendorf et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%